Three generations of international tourist resorts in Mexico - Smith, Jeffrey S. (My University, 2012)
As the world’s leading service sector, international tourism offers developing countries opportunities for lucrative business investment, a major source for foreign currency, and the creation of jobs. Mexico’s leading position among Latin American and Caribbean international tourist destinations rests largely on its concerted efforts to capitalize on the aesthetic appeal of its coastal locations. Over the last 50 years Mexico has witnessed three generations of seaside resorts catering to international visitors. The lessons learned by the Mexican government should be considered by other countries developing large-scale coastal tourism.
Keywords: Mexico; Tourism; International tourist resorts; Acapulco; Cancun; Ixtapa